Data from 617 Healthy Participants Performing the Iowa Gambling Task: A "Many Labs" Collaboration. Issue 1 (24th June 2015) - Steingroever, Helen; Fridberg, Daniel J.; Horstmann, Annette; Kjome, Kimberly L.; Kumari, Veena; Lane, Scott D.; Maia, Tiago V.; McClelland, James L.; Pachur, Thorsten; Premkumar, Preethi; Stout, Julie C.; Wetzels, Ruud; et al.
This data pool (N = 617) comes from 10 studies assessing performance of healthy participants (i.e., no known neurological impairments) on the Iowa gambling task (IGT)—a task measuring decision making under uncertainty in an experimental context. Participants completed a computerized version of the IGT consisting of 95 – 150 trials. The data consist of the choices of each participant on each trial, and the resulting rewards and losses. The data are stored as .rdata, .csv, and .txt files, and can be reused to (1) analyze IGT performance of healthy participants; (2) create a "super control group"; or (3) facilitate model-comparison efforts. A correction article related to the authors of this publication can be found here:http://doi.org/10.5334/jopd.am